Breastfeeding and complementary feeding with stunting among children aged 25-36 months - Markukuh Sri Handayani; Nanik Setiyawati; Yuliantisari Retnaningsih (Jurnal Kesehatan Ibu dan Anak, 2020)
Stunting is a condition of malnutrition that occurs at first 1000 days of birth, so the child looks shorter than his age. Stunting has long-term effects on individuals and societies; including diminished cognitive and physical development reduced productive capacity and poor health. Stunting becomes a big problem for Banyuasin Public Health Center (PHC) because of its high prevalence of 20.3%in 2018. But the achievement of exclusive breastfeeding is low at 66.6%. This study aimed to identify the relationship breastfeeding and complementary feeding with stunting among children aged 25-36 months in Loano Distrik Purworejo Regency, Central Java. This was an analytic observational study with a case-control design. The subjects were mothers and children aged 25-36 months. The sample size used was 88 respondents with 44 as the stunting group and 44 as the control group. Sampling technique with Probability Proportional to Size (PPS). Bivariate analysis using Chi-Square and multivariate using logistic regression. Exclusive breastfeeding (p = 0.000), first complementary feeding time (p = 0.002), age of mother (p = 0.043), and mother's education (p = 0.042) were related with stunting. Whereas mother’s MUAC, mother’s height, and duration of breastfeeding were not related to stunting. The factor that most influences the incidence of stunting is exclusive breastfeeding (OR = 5,36, CI = 2,10-13.67). Exclusive breastfeeding, first complementary feeding time, age of mother, and mother's education are related to stunting. While the variable that most influences the incidence of stunting is exclusive breastfeeding. For this reason, exclusive breastfeeding for infants aged 0-6 months is recommended.